Analisis perhitungan dan pelaporan Pajak Penghasilan (PPh) pasal 21 pada Komisi Pemilihan Umum Kota Tomohon - Kaindeh, Gracia Dineliska; Kalangi, Lintje; Budiarso, Novi Swandari (Yayasan Widyantara Nawasena Raharja, 2025)
Income Tax (PPh) Article 21 is withholding tax on income in connection with service work, or activities in whatever name and form received or obtained by domestic individual taxpayers, which must be carried out by employers, government treasurers, corporate pension funds, companies, and organizing activities. The purpose of this writing is to analyze the calculation and reporting of Income Tax Article 21 at the Tomohon City General Election Commission in accordance with Law no. 7 of 2021. The analytical method used is descriptive qualitative with data collection methods interviews, observation and documentation. The results of the research show that the analysis of the calculation and reporting of Income Tax (PPh) Article 21 at the Tomohon City General Election Commission is not fully in accordance with regulations because Income Tax reporting is only carried out annually and monthly and quarterly reporting is not carried out.